PROSEDUR MEMBERSIHKAN AREA LOUNGE BAR DAN PERALATAN BAR DI HOTEL BERBINTANG KOTA PADANG - Putra, Fiko Nanda; Kasmita, Kasmita; Waryono, Waryono (Journal of Home Economics and Tourism, 2015)
This Study originated from the observation of researchers for researchers doing field work industry (PLI) dated 2 September 2013 againts the working procedure employee Bar is still not good in the Bar and lounge area cleaning equipment Bar. This study aimed to describe the cleaning procedure lounge area and equipment Bar. This type of research is descriptive research with a qualitative approach. Sample data source is employee supervisor Bar and Bar. Data collection techniques is done by observasion, interview and documentation. TheÂ resuts of the study concluded that in general the procedure purge Bar lounge area and Bar equipment in the desert city star hotel is: 1) at the time of cleaning the Bar counter, starting, with the Bolt MPC chemical spraying and wipe with a shine up. 2) clears the Bar station started using metal polish rubbed with sponges soaked with a clean cloth. 3) clears the Bar display starts by using a clean and soft cloth, on a displayglass sprayed using a clean ser and wipe with a Dry Cloth. 4) clean the lounge Bar begins with sweeping and mopping the dirty parts, mendusting tables and chairs, desk and chairs neatly arrange appropriate floor plan or lay out of the lounge Bar. 5) cleaning equipment starting from washing dirty parts with chemical, drain and rinse in polish.Keywords: Cleaning Procedures, a Bar Lounge Area and Bar Equipment